Coágulo, fibrina rica em plaqueta (PRF) ou Bio-OSS em alvéolos frescos: o que utilizar para manutenção aveolar? - Kasaya, Marcus Vinicius Satoru (2017)
After tooth extraction in the anterior maxilla region, alveolar ridge resorption and soft tissue collapse result in aesthetic and functional problems as well as the impediment to the installation of osseointegrated implants. In order to prevent such limitations, it is necessary in the planning of the extraction, the inclusion of regenerative procedures simultaneously to extractions, such as filling the alveoli with Platelet Rich Fibrin (PRF). The objective of this study was to retrospectively evaluate the variations of the alveolar ridge area using computerized tomography after the extraction of maxillary anterior teeth and alveolar filling with PRF, clot and mineralized bovine bone. For this, nine patients were used, which were submitted to extraction of teeth located in the anterior region of the maxilla by a minimally invasive technique and the alveoli filled with: blood clot (COA GROUP); mineralized bovine bone (BIO GROUP) and Rich Fibrin in Platelets (GRUPO PRF). In all groups, an absorbable collagen membrane was sutured over the alveoli. CT scans were performed preoperatively (T1) and seven months after exodontia and filling of the alveolar cavities (T2). For each patient, 3 sections of the preoperative tomography were selected in the sagittal direction and 3 sections of the postoperative tomography corresponding to the center, 1mm medial and 1mm distal from the alveolus were selected. The ImageJ® software was used to measure the changes in the areas of the alveoli from T1 to T2. The values were tabulated and submitted to statistical analysis using the ANOVA test, followed by Holm Sidak (5%). The results showed that there was a significant difference between PRF group (8.79% and +-4.05) and COA group (17.2% and +-1.24), and between BIO and COA groups (6.6% and + -1,20). For a multiple comparison between paired groups, it was found that there is a statistically significant difference between the PRF and COA groups (p = 0.0067), with lower bone absorption in the PRF group.Between the BIO and COA groups were also statistically significant deferred (α = 0.0022), with lower alveolar absorption in the BIO group. Between the BIO and PRF groups there were no statistically significant differentials (p = 0.333). The use of Rich Fibrin in Platelets (PRF) and Bio-Oss in fresh alveoli causes less bone absorption compared to the clot. However, more information should be carried out with larger samples and a combination of biomaterials in order to find an ideal alternative for the preservation of the dental alveolus after the extraction.